The impact of armed conflicts on the environment: contemporary problems of international legal responsibility - Hilevych, O. V.; Shulga, V. O. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
In the scientific article, examines critical issues of the impact of armed conflicts on the environment through the prism of international legal responsibility. Against the backdrop of unprecedented destruction caused by the current war in Ukraine, the authors emphasise an alarming trend: the environment is increasingly turning not only into a theatre of war, but also into a targeted target. This leads to large-scale and long-term environmental disasters, the consequences of which will be felt for decades. The study substantiates the urgent need for a fundamental update of the international legal approach to environmental protection in war, in particular through the introduction and international recognition of the concept of ‘ecocide’ as a separate crime. This will make it possible to bring to justice those responsible for the most serious environmental crimes. The authors conducts a thorough analysis of the current rules of international humanitarian law, including the Geneva Conventions and their additional protocols. The paper highlights the insufficient effectiveness of these norms in the current conditions of military confrontation, where the scale and nature of environmental destruction far exceeds that provided for by existing legislation. The study also focuses on such key forms of international legal responsibility as reparations and satisfaction. They are seen as effective tools not only to compensate for enormous environmental damage, but also to achieve comprehensive justice for affected communities and states. Particular attention is paid to the analysis of the historical precedent - the activities of the UN Compensation Commission after the Gulf War. This mechanism, which provided compensation for environmental damage, is proposed as a viable model for creating a similar mechanism in the Ukrainian context. The introduction of such a mechanism would not only provide the necessary funding for the environmental restoration of Ukraine, but also create a transparent and accountable system of responsibility under the close supervision of international organisations. This scientific article is an important contribution to the development of legal science in the field of environmental protection and international responsibility. It offers concrete, well-reasoned solutions to improve the international legal framework, adapting it to the new, unprecedented challenges faced by the world community in the context of modern wars.